Strong agribusiness, hard worker: case study in the garlic cutting work in Alto Paranaíba - MG - Ribeiro, Janaíne de Fátima; Cunha, Ana Cláudia da Silva; Santos, Igor dos; Campos, Larissa Sousa (Brazilian Journal of Production Engineering, 2024)
Agriculture´s works exposes the workers there to the most diverse types of risk, whether due to the nature of the activity, carried out outdoors and with exposure to adverse weather conditions, or due to the conditions offered to these workers, which impose a high degree of of high-intensity physical effort. In the activity of cutting garlic, this physical effort is concentrated on the hands and wrists and leads to serious consequences for people’s health. This work presents the results of an Ergonomic Work Analysis (EWA) of garlic cutting in the region of Alto Paranaíba- MG, one of the regions with the highest production in the country. In the study, direct observations and interviews were carried out to identify a demand related to the risks present in the work situation, their causes and possible consequences. In the diagnosis, we sought to establish possible correlations between problems as well as priorities of intervention. Finally, some recommendations for improvement and some notes on demands for future studies were drawn up.